O movimento Brasil livre - Freitas, Osires Vinicius Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This paper discusses the Brazilian Free Movement (MBL) from its inception in 2014 to 2016, including the demonstrations in favor of impeachment, which were one of the greatest popular acts in Brazilian history, until the beginning of the campaigns elections for the 2016 municipal elections. It is shown a change of position of the MBL, which tries to approach the state, electing candidates linked to the movement after the removal of President Dilma Rousseff. This study starts from the problematic about the lead of MBL in the change of the way in which the Brazilian political right understands itself and acts in the society. In this context, it is added that those belonging to the right wing of the political spectrum find in the MBL the daily political activism, carried out through the virtual media, but that it was able to mobilize large contingents of individuals who were little engaged in their demands and practically not identified as being part of the political right. Faced with this outlook, the present text runs through the channeling of society's discontent with the State and political parties, in the conversion of this dissatisfaction to a feeling of expectation; for the resolution of corruption, especially the one committed by the Partido dos Trabalhadores (PT-Workers Party); and for the reduction of the tax burden and the oversize of the State, which would be the main Brazilian problems in the MBL's conception. The following analysis includes the importance of social networks in gaining adherents to the movement, in the realization of the manifestations and in the influence of the MBL in the elections

surgimento no ano de 2014 até o ano de 2016, contemplando as manifestações a favor do impeachment, que foram um dos maiores atos populares da história brasileira, até o início das campanhas eleitorais para as eleições municipais de 2016. É mostrada mudança de postura do MBL, que intenta se aproximar do Estado, elegendo candidatos ligados ao movimento após a destituição da presidenta Dilma Rousseff. Este estudo parte da problemática sobre o protagonismo do MBL na mudança da forma com que a direita política brasileira compreende a si mesma e atua na sociedade. Dentro deste contexto, é somado o fato dos pertencentes à direita do espectro político encontrarem no MBL o ativismo político cotidiano, realizado através das vias virtuais, mas que se mostrou capaz de mobilizar grandes contingentes de indivíduos que pouco se engajavam nas suas reivindicações e praticamente não demonstravam identificação como sendo parte da direita política. Diante deste panorama, o presente texto perpassa a canalização do descontentamento da sociedade para com o Estado e os partidos políticos, na conversão desta insatisfação em um sentimento de expectativa; para a resolução da corrupção, em especial, a cometida pelo Partido dos Trabalhadores (PT); e para a diminuição da carga tributária e o excesso de tamanho do Estado, que seriam os principais problemas brasileiros segundo o MBL. A análise, a seguir desenvolvida, examina à importância das redes sociais na conquista de adeptos ao movimento, na realização das manifestações e na influência do MBL nas eleições
Keywords: Movimentos sociais - Brasil; Manifestações públicas; Redes sociais; Demonstrations